Karakteristik Pemimpin Gereja Yang Efektif Dalam Mengantisipasi Masa Depan Gereja (International Forum of Researchers and Lecturers, 2023)
Leadership in the church is not the exercise of human power or authority but an activity of service, service aimed at Jesus Christ. therefore a Christian Leader must have Effective Characteristics. One of the efforts is to make Christian leadership with good character and capable of anticipating the future of the church. namely a leader must lead with integrity and have the ability to lead, serve like Christ. the church has a responsibility in creating leaders with character, a leader is not born but is created because of that a leader, has a character that is committed, good, honest, humble, disciplined to produce such a figure requires a good and right character education so that quality and effective church leaders.